Investigating antibiotics in the NICU and patient safety - Lawrence, Shelley M.; Wynn, James L.; Kimberlin, David W.; Cantey, Joseph B. (Frontiers in Cellular and Infection Microbiology, 2025)
In recent years, a number of observational studies have been published in neonatology-focused journals that modify American Academy of Pediatrics (AAP) evidence-based guidelines, as outlined in the Red Book and other publications authored by the AAP Committee on the Fetus and Newborn and the AAP Committee on Infectious Diseases, for the treatment of neonatal infectious diseases. Specifically, studies that decrease the treatment length or advocate for the early transition of intravenous to oral antibiotics in all neonates with suspected or culture-positive sepsis or pneumonia should be regarded with caution. These studies are usually conducted through quality improvement initiatives without informed parental consent, and lack well-defined definitions for the infection of interest. They often fail to include sufficient information regarding well-documented variations in gestational age-based immune responses, and usually combine bacterial infections into a single group without considering virulence and pathophysiologic differences between gram-negative and gram-positive infections. We seek to raise awareness of the potential harm these practices may cause and to advocate for parental involvement and consent when deviations from practice standards are investigated.